The Transformation of Aesthetics in Architecture from Traditional to Modern Architecture: A case study of the Yoruba (southwestern) region of Nigeria - Femi Emmanuel Arenibafo (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
Aesthetics is the philosophical study of art and natural beauty and it is indicated by the feelings of pleasure or displeasure which comes from visual and aural elements and artefacts. Hence, aesthetics depends on the animate or inanimate organization which can be perceived either subjectively or objectively. This aesthetic element is uniquely present in the traditional buildings and modern buildings of the southwestern part of Nigeria. This study is set out to evaluate and bring into limelight the aesthetic characteristics of traditional buildings and that of the modern buildings, how one style or aesthetic element gradually prevail over or transform to another, reasons and consequences of one completely predominating another in Yoruba region of Nigeria. Moreover, this study therefore, is divided into four parts, which are: (a) overview of the history of modern and traditional Architecture of Yoruba land (b) aesthetic characteristics or indicators of traditional and modern architecture in Yoruba land, (c) the differences between the aesthetic of both styles of Architecture and what is responsible for this change or transformation in their aesthetic value. The research concludes with recommendations of synchronizing both styles of architecture design in getting an optimum aesthetic value and offers a room for further research and development of a consistent and notable architectural typology for southwest Nigeria.